THE EFFECT OF E-COMMERCE AND CORPORATE IMAGE ON CUSTOMER SAVING DECISIONS IN PT BANK RAKYAT INDONESIA PAREPARE BRANCH - Dewi Kartikasari; Ulyana Muslimin (Jurnal Telekomunikasi dan Informatika, 2023)
This study aims to determine whether e-commerce and corporate image have a partial and simultaneous effect on customers' saving decisions at PT Bank Rakyat Indonesia Parepare Branch. The sample in this study were customers who made saving stransactions at PT Bank Rakyat Indonesia, Parepare Branch, with a total of 60 people. The sampling method was carried out using the Roscoe approach to the technique used in this study (accidental sampling). Methods of data collection used are questionnaires, interviews, documentation, and observation. The method of analysis utilized in this study is validity test and reliability test, descriptive analysis, t test and f test, Multiple linear regression analysis and determination coefficient using SPSS V.24. The findings of this research indicate that the t test of the e-commerce variable (X1) has a positively influences the decision to save (Y) because the value shows (2.305≥2.002) and there is a partially complete significant influence between the e-commerce variables, while the corporate image variable (X2) has a positive effect on saving decisions (Y), because the value shows (3.443≥2.002), this shows that corporate image has a considerable influence on saving decisions at PT Bank Rakyat Indonesia Parepare Branch. Furthermore, the f test's findings state that simultaneously the e-commerce variable and corporate image have an important impact on saving decisions because Fcount>Ftable where the value is (6.239>3.16). This also indicates that the independent factors have an effect on the dependent variable.